Design of power distribution network for efficient microgrid operation - Tan, Junming (2014)
A microgrid consists of several electric power generators that supply electricity and heat to a group of customers. Microgrids can be consist of a limited number of residential homes that are interconnected with each other and form an isolated power system independent from the large utility grid.